2015
DOI: 10.3390/molecules20046273
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective Triterpene Saponins from the Roots of Glycyrrhiza inflata

Abstract: Two novel oleanane-type triterpene saponins, licorice-saponin P2 (1) and licorice-saponin Q2 (3), together with nine known compounds 2, 4–11, have been isolated from the water extract of the roots of Glycyrrhiza inflata. The structures of these compounds were elucidated on the basis of spectroscopic analysis, including 2D-NMR experiments (1H–1H COSY, HSQC, HMBC and ROESY). In in vitro assays, compounds 2–4, 6 and 11 showed significant hepatoprotective activities by lowering the ALT and AST levels in primary ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 15 publications
(19 reference statements)
0
31
0
Order By: Relevance
“…Phytochemical studies showed that over 300 diverse compounds have been identified from the genus Glycyrrhiza [ 2 , 3 , 4 , 5 ]. Among them, triterpenoids and flavonoids were the two major active substances, exerting a variety of pharmacological activities including antiviral [ 6 , 7 , 8 ], anti-inflammatory [ 9 , 10 , 11 , 12 ], antioxidative [ 13 , 14 ], hepatoprotective [ 15 , 16 ], antimicrobial [ 17 , 18 , 19 , 20 , 21 , 22 ], antitumor [ 23 , 24 , 25 ], antiallergic [ 26 , 27 , 28 ], and potent cytochrome P450 enzyme inhibitory [ 29 ] properties. To what extent these components are effective in the human body depends on their bioavailability and metabolism in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Phytochemical studies showed that over 300 diverse compounds have been identified from the genus Glycyrrhiza [ 2 , 3 , 4 , 5 ]. Among them, triterpenoids and flavonoids were the two major active substances, exerting a variety of pharmacological activities including antiviral [ 6 , 7 , 8 ], anti-inflammatory [ 9 , 10 , 11 , 12 ], antioxidative [ 13 , 14 ], hepatoprotective [ 15 , 16 ], antimicrobial [ 17 , 18 , 19 , 20 , 21 , 22 ], antitumor [ 23 , 24 , 25 ], antiallergic [ 26 , 27 , 28 ], and potent cytochrome P450 enzyme inhibitory [ 29 ] properties. To what extent these components are effective in the human body depends on their bioavailability and metabolism in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Triterpene saponins were the main constituents of Glycyrrhizae radix et rhizoma , and performed a variety of pharmacological activities 16 17 18 . In this work, 22 oleanane triterpene saponins were identified in the extract of GZJSYT.…”
Section: Resultsmentioning
confidence: 99%
“…196 Licoricesaponins P2 and Q2 are saponins from Glycyrrhiza inata with the new genins 595 and 596, respectively. 197 Genin 596 has an unusual 18aH. Other oleanane saponins with new genins include 22-acetyluralsaponin C from Glycyrrhiza uralensis with genin 597, 198 204 New oleanane saponins with known genins that have been assigned trivial names are listed in Table 1.…”
Section: The Lupane Groupmentioning
confidence: 99%